Sterilization Devices In Infection Control: Effectiveness, Prioritization, And Clinical Impact In Healthcare Settings (The Review of Diabetic Studies, 2024)
BackgroundSterilization forms the cornerstone of infection control in healthcare, eliminating all microbial life, including spores, from reusable critical and semicritical devices to prevent healthcare-associated infections (HAIs) like CLABSIs and VAPs, which affect 5-30% of patients and drive substantial morbidity, mortality, and costs. Technologies such as steam autoclaving, ethylene oxide (EtO), hydrogen peroxide plasma, and emerging plasma systems address multidrug-resistant organisms (MDROs) and biofilms per Spaulding classification, amid rising antimicrobial resistance.​MethodsThis narrative review synthesized peer-reviewed evidence on sterilization devices' effectiveness, prioritization, and clinical impact, focusing on reusable devices in operating rooms, ICUs, and CSSDs. Data encompassed laboratory log reductions (>6-log10 for spores), clinical HAI reductions, cost-benefit analyses, outbreak case studies, and guidelines from CDC, WHO, and ISO standards, evaluating factors like cycle time, material compatibility, and environmental safety.​ResultsSteam autoclaving excelled in efficacy and speed for surgical instruments, while low-temperature hydrogen peroxide and plasma suited heat-sensitive endoscopes, achieving sterility assurance levels of 10^{-6} and reducing HAIs by up to 70% via odds ratios of 0.30. Prioritization via risk assessment (e.g., FMEA) and precleaning lowered bioburden by 4-6 log10, with innovations like AI monitoring cutting errors by 40-50%; however, human factors and biofilms posed challenges, alongside EtO's toxicity.​ConclusionsOptimized sterilization prioritization enhances patient safety, curtails HAIs and costs (e.g., $642,010 savings per facility), and supports antimicrobial stewardship, urging adoption of eco-friendly, digital-integrated technologies and rigorous training.